Diagnostic and Prognostic Relevance of Circulating microRNAs across Multiple Cancer Types - Ghea Farmaning Thias Putri; Firda Asmaul Husna; Dwi Widyawati; Zahara Nurfatihah Z (Pattimura University, 2025)
Cancer represents a global health burden characterized by high morbidity and mortality,underscoring the urgent demand for reliable, non-invasive biomarkers to enhance early detection,prognostication, and therapeutic monitoring. Circulating microRNAs (c-miRNAs) are short non-coding RNAs present in body fluids that have attracted attention as potential biomarkers, because of their stability, ease of detection, and close relationship with tumor biology. This review evaluates the diagnostic and prognostic potential of c-miRNAs and their integration into precision oncology. A systematic search was performed across PubMed, Scopus, and ScienceDirect for publications from 2010 to 2025 that investigated c-miRNAs in human body fluids in relation to diagnosis, prognosis, or treatment response. Twelve studies met the eligibility criteria, encompassing breast, lung, colorectal, and gallbladder cancers. Frequently dysregulated c-miRNAs, particularly miR-21, miR-155, miR-210, and Let-7a, demonstrated consistent associations with tumor detection, patient survival, and disease progression. Analytical platforms ranged from quantitative RT-PCR to advanced biosensor-based technologies, enabling sensitive and rapid quantification. Collectively, the evidence highlights c-miRNAs as non-invasive biomarkers capable of complementing conventional clinical tools. Their clinical adoption could reduce reliance on invasive tissue biopsies, support earlier and more accurate diagnosis, assist in tailoring patient-specific treatment strategies, and promote the broader implementation of precision medicine in cancer care.